(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Today, by implementing the strategy of spiritual and cultural reforms in New Uzbekistan, increasing the spiritual and educational level of our people, together with social, economic and political factors, delivering the reforms implemented in the spiritual and educational spheres to the people.